2015
DOI: 10.18632/oncotarget.4577
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin combined with FAPαc vaccine elicits effective antitumor response by targeting indolamine-2,3-dioxygenase and inhibiting EMT induced by TNF-α in melanoma

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…Our experiments showed that the presence of diabetes led to elevated expression of TNF-α, IL-6 and p-NFκB in tumor tissues. These inflammatory factors promote tumor growth, exert anti-apoptotic activities and induce EMT [2224]. Figures 5 and 8 show that SB203580 significantly downregulated these inflammatory factors in vitro and in vivo , inhibited tumor growth and metastasis and significantly prolonged the survival of mice with pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments showed that the presence of diabetes led to elevated expression of TNF-α, IL-6 and p-NFκB in tumor tissues. These inflammatory factors promote tumor growth, exert anti-apoptotic activities and induce EMT [2224]. Figures 5 and 8 show that SB203580 significantly downregulated these inflammatory factors in vitro and in vivo , inhibited tumor growth and metastasis and significantly prolonged the survival of mice with pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin inhibited migration and decreased expression of MMP-2 and MMP-9 in A375 cells, and these effects were associated with decreased phosphorylation of JAK-2 and STAT-3 [175]. Curcumin also blocked TNF-α-induced upregulation of EMT markers in B16 cells; treated cells expressed less vimentin and more E-cadherin than controls [176]. Other studies have confirmed that treatment with curcumin decreased migration of B16F10 cells through collagen matrices via inhibition of MMPs [177].…”
Section: Phytochemicals With Known Anti-emt Propertiesmentioning
confidence: 99%
“…We demonstrated that FAP α vaccine combined with curcumin lavage inhibits tumor growth and prolongs the survival of mice implanted with melanoma cells. The combination of a FAP α vaccine and curcumin stimulated FAP α antibody production and CD8+T cell-mediated killing of FAP α-expressing stromal cells without adverse reactive effects [9]. These results suggest that FAP α, a product preferentially expressed by CAFs, would be a more effective antigen to target in the setting of cancer immunotherapy.…”
Section: The Fap α-Targeted Immunotherapy Strategymentioning
confidence: 99%
“…Therefore, FAP α expressing cells are a non-redundant, immunosuppressive component of the TME [8]. Furthermore, it was reported that a FAP α vaccine combined with curcumin stimulates FAP α antibody production and CD8+ T cell-mediated killing of FAP α-expressing stromal cells and prolongs the survival of mice implanted with melanoma [9]. All of these results suggest that FAP α is an adaptive tumor-associated antigen useful for tumor immunotherapy.…”
Section: Introductionmentioning
confidence: 99%